RELATIONSHIP BETWEEN ENVIRONMENT AND COMMUNITY BEHAVIOR AGAINST DENGUE HEMORRHAGIC FEVER AT GATAK HEALTH CENTER - Dewi Yuli Astuti; Fajar Alam Putra; Ahmad Syamsul Bahri (Universitas Sahid Surakarta, 2019)
Background: This research was conducted in the working area of the Gatak comunity health center which was related tho the level of dengue (DBD). Dengue hemorrhagic fever (DBD) is a disease caused by infection with the virus DEN-1, DEN-2, DEN-3,or DEN-4. To prevent level the occurrence of dengue fever it is necessary to pay attention to the surrounding environment and comunity behavior. Purpose: This study aims to determine the relationship of the environment and the relationship of community behavior to the incidence of dengue hemorrhagic fever (DHF) in the Gatak Health Center Work Area. Method: Type of analytic survey research with case control research design.. The study population used as many as 70 people, with a total sample of 70 respondents sensu sampling teshnigues. Results: discussion can be obtained that (1) the results of chi square analysis X2 count at = 15,313> X2 table = 3,841 and P value of 0,000 X2 table = 3,841 and P value of 0,000